Nilai-Nilai Karakter dalam Permainan Tradisional Pecah Piring - Umri Rahman Efendi; Daulat Saragi; Yakobus Ndona (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Teachers have used various methods to implement good character education, including demonstration methods, questions and answers, lectures and assignments. It turns out that this still does not have a significant impact on children's character and growth and development, therefore teachers as educators use alternative learning with traditional games which in the learning process are in accordance with the interests of students who always want to play. The game of breaking plates is one of the traditional children's games that is often found in the Medan city area and its surroundings. The sample for this research was all students in class VI A at SDN 101786 Helvetia, totaling 35 students. The instruments used are observation and value surveys. Character values ​​of honesty, religion, discipline/sportsmanship, hard work, responsibility. The results of the research showed that the children in class VI A had demonstrated character values ​​well and were able to implement them during the plate breaking game..